Forming Students with Superior Character in the 21st Century for the Future of Indonesian Citizenship - Gunawan Santoso; Aim Abdulkarim; Bunyamin Maftuh; Sapriya Sapriya; Meilanta Rantina; Ma'mun Murod (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Building 21st century character skills is not easy. Industrial revolution 5.0. brought major changes to the industrial world, which then influenced the way of life, way of thinking, way of working, and so on. The goal is to cultivate knowledge, attitudes and sensitivity in the practice of life values needed to build superior national character skills in the 21st century. Design/methodology/approach: Qualitative methods are grounded approach types, namely observation, literature study, and interviews: namely interviews with various stakeholders such as professors, lecturers, teachers, education experts, business people, experts, students, from July 8-11 2022, attended by 112 resource persons consisting of lecturers and students, and attended by 53 universities. Findings: The results of his research through four elements, namely; First, the character habituation of Pancasila values, religious values, and cultural values; Second, habituation of understanding the latest technology; Third, habituation of developing interpersonal skills; Fourth, Habituation of active participation. This is currently typical of Indonesia, superior character skills based on the 21st century revolution 5.0 as the vision and mission of Citizenship Education for the Republic of Indonesia in the future. Paper type: Research paper